Formulasi Lilin Aromaterapi Kombinasi Minyak Atsiri Kulit Jeruk Nipis (Citrus aurantifolia) Dan Bunga Melati (Jasminum sambac L.) Dengan Cera Alba Sebagai Basis - Agustina Putri Pitarisa Sudarsono; Aulia Avida Ramanda (Jurnal Farmasi & Sains Indonesia, 2025)
Aromatherapy is an alternative treatment method that utilizes volatile essential oils to provide therapeutic Aromatherapy is an alternative treatment method using volatile essential oils to provide therapeutic effects such as relaxation and improved blood circulation. Lime peel essential oil contains limonene as a repellent, while jasmine flower essential oil contains linalool that promotes calmness. Cera alba is used as a candle base to support structure and burning stability. This study aimed to evaluate the effect of combining lime peel and jasmine essential oils with varying cera alba concentrations on the physical properties and acceptability of aromatherapy candles. Five candle formulas were prepared: F0 without essential oils as a control, and F1–F4 with varying concentrations of lime peel (0.1–0.3%) and jasmine (7–9%). Evaluations included organoleptic tests, melting point, burning time, and hedonic tests by panelists. Results showed that essential oil combinations influenced melting point, burning time, and aroma. Formula F3 (lime peel 0.2%, jasmine 7%, cera alba 82.8%) met all physical standards with an average melting point of 57°C, burning time of 168.67 minutes, and was most preferred by panelists. Statistical analysis confirmed normality and homogeneity, and post hoc tests (p < 0.05) indicated significant differences among formulas, demonstrating that essential oil combination and cera alba concentration determine candle quality and panelist preference.